(untitled) (Global Journal of Sciences, 2025)
Many fields of the physical sciences like physics, chemistry and mathematics use partial differential equations to model a physical system. As a result, there are diverse techniques in the literature for the solution of partial differential equations which tries to attain symmetry. This paper proposes a fresh double transform method recognized as the double Mohand Transform Method. Besides the explanation and major remarks of the proposed double transform method, new results on partial derivatives are also given. Moreover, to validate the importance of the double Mohand Transform Method in solving systems of partial differential equations, a variety of symmetric examples on the wave equation with various properties are solved using this approach.